Hastened Death and the Regulation of the Practice of Medicine - Ronald A. Lindsay; Rebecca P. Dick; Tom L. Beauchamp (Washington University Journal of Law & Policy, 2006)
We begin with a summary of the controversy over legalized assistance in hastening death and a description of how that controversy led to Gonzales v. Oregon. We then review the Gonzales decision, explaining what it did and did not resolve. Looking to how these issues should be analyzed in the future, we will explain why a fundamental distinction currently embedded in the law is unhelpful in analysis of the legitimacy of assistance in hastening death. We will argue that, correctly understood, assistance in hastening death is properly regarded as a medical practice, or, more broadly stated, that a physician legitimately may assist in various ways in helping to bring about the death of a terminally ill patient who has explicitly and competently requested this assistance from the physician. In making this argument, we suggest how these and other disputes over medicine’s boundaries should be resolved.
Keywords: Assisted suicide; Medical ethics; Narcotic laws; Prescriptions (Drugs); Terminally ill persons; Treatment refusal; Controlled Substances Act of 1970; Oregon. Death with Dignity Act; Oregon; United States